Exploring the impact of oral health-related quality of life on the child's family structure - Patrícia Santos; Felipe Alexandre de Souza; Diego Patrik Alves Carneiro; Marcelo de Castro Meneghim; Silvia Amélia Scudeler Vedovello (Universidade Estadual de Campinas, 2020)
Aim: The aim of this study was to explore the impact of oral health-related quality of life (OHRQoL) on the child's family structure. Methods: A representative sample of 613 children from public preschools, in a city in southeastern Brazil, were enrolled in this cross-sectional study. The sample was determined through probabilistic sampling in two stages (preschools and children). The outcome variable (Early Childhood Oral Health Impact Scale [ECOHIS]) was multi-categorized in children and family. Independent individual variables were sex, race, family income, parents'/caregivers' level of education, family income, dental caries, and malocclusion. Initially, individual analyses were performed, relating the study variables to the outcome variables, estimating the raw odds ratio with the respective confidence intervals of 95%. The variables with p < 0.20 in the individual analyses were tested in the multiple logistic regression models, and those with p < 0.10 remained in the model. Results: Impact on OHRQoL was reported by 40.9% of the children and 17% of their families. Children with low family income and caries experience had, respectively, 1.53 (95% CI: 1.00-2.32) (p = 0.0465) and 2.96 (95% CI: 1.81-4.84) (p < 0.0001) more chance of presenting negative impact on OHRQoL. Conclusions: The aspects that most affected the OHRQoL of child's family structure were low income and dental caries experience.